2020
DOI: 10.1109/access.2020.2985749
|View full text |Cite
|
Sign up to set email alerts
|

A Study on an Anthropomorphic Car-Following Strategy Framework of the Autonomous Coach in Mixed Traffic Flow

Abstract: In this study, to explore the demand characteristics of autonomous coaches in mixed traffic flow, two sections of an expressway were selected for vehicle experiments. With personification as the goal, sensors of the ego-vehicle were used to collect naturalistic car-following behavior data of surrounding coaches. After analyzing the naturalistic car-following data, car-driving behavior characteristics of the coach drivers were acquired. The analysis results indicate that the overall car-following processes of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Using this perspective, the authors developed a measure proportional to the perceived risk if a hazard's consequences remain unchanged (e.g., collision with the same obstacle). Other researchers have found that the values of time-to-collision (TTC) or time headway when following a vehicle or approaching a slower obstacle highly correlate with a driver's perception of a collision (Vogel, 2003 ; Chen et al, 2016 ; Zhao et al, 2020 ). Researchers have particularly investigated TTC in the literature and have demonstrated that it is directly perceived through retinal expansion (Lee, 1976 ; Bootsma et al, 1997 ; Bootsma and Craig, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using this perspective, the authors developed a measure proportional to the perceived risk if a hazard's consequences remain unchanged (e.g., collision with the same obstacle). Other researchers have found that the values of time-to-collision (TTC) or time headway when following a vehicle or approaching a slower obstacle highly correlate with a driver's perception of a collision (Vogel, 2003 ; Chen et al, 2016 ; Zhao et al, 2020 ). Researchers have particularly investigated TTC in the literature and have demonstrated that it is directly perceived through retinal expansion (Lee, 1976 ; Bootsma et al, 1997 ; Bootsma and Craig, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…From literature reviews, much research has been conducted on mixed traffic flow modeling to study its characteristics under normal weather conditions. Some studies focused on the headway of the CAVs during the car-following process to describe the longitudinal dynamics of the mixed traffic [7][8][9]. Some studies focused on the possible impact of autonomous vehicles on traffic flow and found that the traffic throughput increases at a high CAV penetration rate [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As a typical representative of intelligent machines, the degree of humanoid driving of AVs has attracted more attention. However, studies focus on humanoid control strategies [23,24] and lack quantitative evaluation indexes of the humanoid nature of the driving process. The anthropomorphic level of AVs mainly affects two aspects.…”
Section: Introductionmentioning
confidence: 99%